2021
DOI: 10.1523/eneuro.0298-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

cAMP at Perinuclear mAKAPα Signalosomes Is Regulated by Local Ca2+ Signaling in Primary Hippocampal Neurons

Abstract: The second messenger cyclic adenosine monophosphate (cAMP) is important for the regulation of neuronal structure and function, including neurite extension. A perinuclear cAMP compartment organized by the scaffold protein muscle A-kinase anchoring protein α (mAKAPα/AKAP6α) is sufficient and necessary for axon growth by rat hippocampal neurons in vitro . Here, we report that cAMP at mAKAPα signalosomes is regulated by local Ca 2+ signaling that mediates activity-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…These multi-functional scaffold proteins have been widely characterized in neurons, both in physiological and pathological states (Wild and Dell'Acqua, 2018 ). The AKAPs associated with cAMP are regulated by local Ca 2+ oscillations (Scott and Santana, 2010 ; Boczek et al, 2021 ). Global analysis of astroglial transcripts released in 2015 demonstrated that cAMP-dependent signaling regulated 6,221 of 16,594 annotated genes, including 42.1% of them were significantly upregulated whereas the remaining were downregulated by cAMP analogs.…”
Section: Introductionmentioning
confidence: 99%
“…These multi-functional scaffold proteins have been widely characterized in neurons, both in physiological and pathological states (Wild and Dell'Acqua, 2018 ). The AKAPs associated with cAMP are regulated by local Ca 2+ oscillations (Scott and Santana, 2010 ; Boczek et al, 2021 ). Global analysis of astroglial transcripts released in 2015 demonstrated that cAMP-dependent signaling regulated 6,221 of 16,594 annotated genes, including 42.1% of them were significantly upregulated whereas the remaining were downregulated by cAMP analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Like the shorter CaBP1 variants, caldendrin could bind to and inhibit inositol 1,4,5 trisphosphate receptors (IP 3 Rs) 46 , 47 and therefore IP 3 R-mediated Ca 2+ signals that are known to enhance DRGN neurite outgrowth 48 . Alternatively, caldendrin might interact with the actin-binding protein cortactin 17 and A-kinase anchoring proteins (AKAPs) 49 , both of which have been implicated in neurite growth regulation 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Like the shorter CaBP1 variants, caldendrin could bind to and inhibit inositol 1,4,5 trisphosphate receptors (IP 3 Rs) (Haynes et al, 2004; Kasri et al, 2004) and therefore IP 3 R-mediated Ca 2+ signals that are known to enhance DRGN neurite outgrowth (Takei et al, 1998). Alternatively, caldendrin might interact with the actin-binding protein cortactin (Mikhaylova et al, 2018) and A-kinase anchoring proteins (AKAPs) (Gorny et al, 2012), both of which have been implicated in neurite growth regulation (Boczek et al, 2021; Kubo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%